Vector bionomics and malaria transmission along the Thailand‐Myanmar border: a baseline entomological survey. Issue 1 (June 2017) - Kwansomboon, N.; Chaumeau, V.; Kittiphanakun, P.; Cerqueira, D.; Corbel, V.; Chareonviriyaphap, T.
ABSTRACT: Baseline entomological surveys were conducted in four sentinel sites along the Thailand‐Myanmar border to address vector bionomics and malaria transmission in the context of a study on malaria elimination. Adult Anopheles mosquitoes were collected using human‐landing catch and cow‐bait collection in four villages during the rainy season from May‐June, 2013. Mosquitoes were identified to species level by morphological characters and by AS‐PCR. Sporozoite indexes were determined on head/thoraces of primary and secondary malaria vectors using real‐time PCR. A total of 4, 301 anopheles belonging to 12 anopheline taxa were identified. Anopheles minimus represented >98% of the Minimus Complex members (n=1, 683), whereas the An. maculatus group was composed of two dominant species, An. sawadwongporni and An. maculatus . Overall, 25 Plasmodium ‐positive mosquitoes (of 2, 323) were found, representing a sporozoite index of 1.1% [95%CI 0.66–1.50]. The transmission intensity as measured by the EIR strongly varied according to the village (ANOVA, F=17.67, df=3, P<0.0001). Our findings highlight the diversity and complexity of the biting pattern of malaria vectors along the Thailand‐Myanmar border that represent a formidable challenge for malaria control and elimination.